156 Discovery of TSC-100: A natural HA-1-specific TCR to treat leukemia following hematopoietic stem cell transplant therapy. (9th November 2020) - Nayar, Ribhu; Jangalwe, Sonal; Jurewicz, Mollie; Boudot, Antoine; Basinski, Andrew; Prenovitz, Robert; Olesin, Elizabeth; Pollacksmith, Daniel; Xu, Qikai; Wang, Yifan; Virbasius, Amy; Li, Jeffery; et al.
Abstract : Background: Approximately 30–40% of AML patients relapse following allogeneic hematopoietic stem cell transplant therapy, leaving them with very few treatment options. 1 2 Rare patients that naturally develop an HA-1-specific graft-versus-leukemia T cell response, however, show substantially lower relapse rates. 3 4 HA-1 (VLHDDLLEA, genotype RS_1801284 A/G or A/A) is an HLA-A*02:01-and hematopoietically restricted minor histocompatibility antigen, making it an ideal candidate for TCR immunotherapy for liquid tumors. 5 Methods: We developed a high-throughput TCR discovery platform that enables rapid cloning of antigen-specific TCRs from healthy donors. We then used this platform to screen 178.3 million naïve CD8+ T cells from six unique HA-1- (VLRDDLLEA, genotype RS_1801284 G/G) donors, identifying 329 HA-1-specific TCRs. We tested each TCR for expression and the ability to kill HA-1+ target cells, using a previously published, clinical-stage HA-1-specific TCR as a benchmark for these studies. 6 In parallel, we tested TCR constant region modifications to promote expression and proper pairing of exogenous TCR alpha and beta chains and designed a lentiviral vector to co-deliver CD8 coreceptors as well as a CD34 enrichment tag to enable purification of engineered T cells. The top 11 candidates were cloned into our optimized backbone and evaluated for cytotoxicity, cytokine production, and T cell proliferation using a panel of HLA-A*02:01+ HA-1+ cell lines. Finally, the top two TCRs were evaluated for allo-reactivity and off-target cross-reactivity using our proprietary genome-wide T-Scan platform. Results: The TCR discovery and evaluation platform described here identified 329 HA-1-specific TCRs from a total of 178.3 million naïve T cells, and TSC-100 as the most active TCR. Defined mutations in the constant region of TSC-100 enhanced its surface expression while decreasing expression of endogenous TCRs, and co-introduction of CD8 enabled efficient engagement and function of engineered CD4 cells. Overall, TSC-100 exhibited comparable activity to a clinical-stage benchmark TCR when challenged with cell lines expressing moderate to high levels of HA-1, and superior activity when incubated with cell lines expressing low levels of both HA-1 and MHC-I. 6 In addition, TSC-100 exhibited no detectable allo-reactivity to 108 different HLA types tested, and minimal off-target effects when challenged with a genome-wide library expressing peptides derived from human proteins. Conclusions: TSC-100 exhibits comparable or superior activity to a clinical-stage therapeutic TCR, with minimal allo-reactivity or off-target effects. Based on these results, TSC-100 has been advanced to IND-enabling activities to prepare for first-in-human testing in 2021. Ethics Approval: All clinical samples used in the study were collected by STEMCELL Technologies, StemExpress and HemaCare using their IRB approved protocols. References: Pavletic SZ, Kumar S, Mohty M, et al. NCI First International Workshop on the Biology, Prevention, and Treatment of Relapse After Allogeneic Hematopoietic Stem Cell Transplantation: Report from The Committee on the Epidemiology and Natural History of Relapse following Allogeneic Cell Transplantation. Biol Blood Marrow Transplant . 2010;16(7):871–890. Miller JS, Warren EH, van den Brink MR, et al. NCI First International Workshop on The Biology, Prevention, and Treatment of Relapse After Allogeneic Hematopoietic Stem Cell Transplantation: Report from the Committee on the Biology Underlying Recurrence of Malignant Disease following Allogeneic HSCT: Graft-versus-Tumor/Leukemia Reaction. Biol Blood Marrow Transplant 2010;16(5):565–586. Marijt WAE, Heemskerk MHM, Kloosterboer FM, et al. Hematopoiesis-restricted minor histocompatibility antigens HA-1- or HA-2-specific T cells can induce complete remissions of relapsed leukemia. PNAS 2003;100:2742–2747. Spierings E, Kim Y, Hendriks M, et al. Multicenter analyses demonstrate significant clinical effects of minor histocompatibility antigens on GvHD and GvL after HLA-Matched related and unrelated hematopoietic stem cell transplantation. Biol Blood Marrow Transplant 2013; 19: 1244–1253. Bleakley M, Riddell SR. Exploiting T cells specific for human minor histocompatibility antigens for therapy of leukemia. Immunol Cell Biol 2011;89(3):396–407. Dossa RG, Cunningham T, Sommermeyer D, et al. Development of T-cell immunotherapy for hematopoietic stem cell transplantation recipients at risk of leukemia relapse. Blood 2018;131(1):108–120.